Determinan Penggunaan Media Sosial, Kreativitas dan Pelatihan Terhadap Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Coffee shop di Kota Bekasi - SRI YANTHY YOSEPHA (Universitas Serang Raya, 2021)
Abstract UMKMs are productive economic businesses that stand alone, which are carried out by individual or business entities that are not subsidiaries in order to get benefits. At the time of this pandemic, Bekasi City UMKMs had to struggle to develop products in order to survive. This study aims to determine the effect of using social media and creativity and training on the development of micro, small and medium-sized coffee shops in the city of Bekasi. The formulation of the problem in this research is: Is there any effect of variables on social media, creativity and training partially and simultaneously on business development. The purpose and benefit of this is knowing the partial and simultaneous effect of the independent variable on the independent variable. This study used a sample consisting of 100 respondents. The data analysis technique used normality test, multiple linear regression, t test, F test with quantitative research type and the data sources used were primary and secondary. The results of this study indicate that the use of social media partially affects business development, creativity partially affects business development, but training has no effect on business development. The social media, creativity and training simultaneously affect business development with a coefficient of determination of 48 ,1% while 51.9% is explained by other variables not examined. Keywords: Social Media, Creativity, Business Development, and Training